Godsdiens en Christelike teologie in die skadu van menslike outonomie: wetenskapsfilosofiese verkenninge - W. J. Richards (Acta Theologica)
The phenomenon of religion was often regarded in “scientific” religious studies as something of which the essence and origin was purely human. Psychologists and sociologists of religion inter alia often thought they could fully explain religion in pure human and scientific terms. Later on even historians and phenomenologists of religion etc became convinced (on similar immanentistic grounds) that there was more to it, and that other disciplines such as philosophy and theology were needed in the last resort to come closer to an explanation by introducing transcendental evidence and views. Religion, they were convinced, could not be explained in terms of evidence derived from mere facts or disciplines operating on purely empirical levels within a one-dimensional world.